KEBIJAKAN WALI KOTA MEDAN TENTANG PENANGANAN DAN PENGENDALIAN COVID-19 BERUPA PPKM LEVEL 4 DAN DAMPAKNYA TERHADAP UMKM (USAHA MIKRO KECIL DAN MENENGAH) DITINJAU DARI MAQOSID ASY-SYARIAH DAN USHUL FIKIH - Deniansyah Damanik (TAQNIN: Jurnal Syariah dan Hukum, 2022)
The Mayor of Medan in handling and controlling Covid-19, one way is to carry out PPKM Level 4. This is done because the City of Medan was once included in the red zone. This was done to prevent the spread of the corona virus. On the other hand, the PPKM Level 4 policy has an impact on MSMEs (Micro, Small and Medium Enterprises), because of that the Medan Mayor's policy will have an impact on MSMEs will be reviewed from Maqosid Asy-Syariah and Ushul Fiqh. The two analytical tools will provide an overview of the status of the Mayor of Medan's policy that is actually allowed and feasible to implement or not. Keywords: Mayor of Medan, UMKM, Maqosid Asy-Syariah, Ushul Fikih